Influence of vegetable fats on concrete of agricultural structures - Tsyhanenko, Liudmyla; Volkov, Dmytro; Shkromada, Oksana; Tsyhanenko, Hennadii; Lutskovskyi, Valerii; Shpota, Vadym; Reznichenko, Yevhen (Technology audit and production reserves, 2025)
The object of the study was concrete samples with different penetration depths of vegetable oil. For the experiment, concrete samples were taken from the foundation for the oil pan equipment, in the form of cylinders with a diameter of 100 mm and a height of 200 mm. It was found that the experimental sample No. 1 has a decrease in compressive strength of about 6 %, sample No. 2 has a decrease in strength of about 19–20 %, sample No. 3 has a decrease in strength of about 48 % from the control sample No. 4. The study using scanning electron microscopy showed the presence of a layer of solidified oil and plant residues on the surface of the concrete samples. Mycelium of microscopic fungi was detected at a depth of 2 cm from the surface. The study of concrete samples using TPD MS showed that CO was intensively released at a temperature of 583 °C from samples 2 – 0.03 and 3 – 0.05. At a temperature of 552 °C, CO2 was released with an intensity of 0.1 from sample 2 and 0.18 from sample 3. In other samples, carbon was not released, which is associated with biochemical corrosion of concrete. At a temperature of 100 °C, H2O was released from concrete samples 2 – 0.8 and 3 – 0.4. Sulfur was released when heated to 90 °C from sample 4_2 in insignificant quantities – 0.0035. SO was released from samples 2 (0.014), t=764 °C and 3 (0.012) t=809 °C. Sulfur dioxide was released at a temperature of 794 °C with an intensity of 0.005 from samples 2 and 3. The conducted study is distinguished by the fact that correlations were established between the depth of oil impregnation of concrete and loss of strength. Destructive changes in concrete samples, the presence of a layer of solidified oil and microscopic fungi were detected. The presence of carbons, sulfur and its oxides in concrete samples that were least damaged by corrosion processes is associated with the composition of sulfur concrete to give it greater strength. The practical significance of the results obtained is that the negative influence of vegetable fats on concrete is proven, namely a decrease in strength, destruction of the microstructure and the growth of microscopic fungi.